MATHEMATICAL MODELING FROM THE EYES OF PRESERVICE TEACHERS - Sener, Zehra Taspinar; Dede, Yuksel (CLAME-COMITE LATINOAMERICANO MAT EDUC, 2021)
Using preservice teachers' ( PTs) opinions as its base, this study seeks to shed light on the process followed by PTs in teaching mathematical modeling to middle school students. The study group was composed of 18 middle school mathematics PTs, each of whom was selected using purposeful sampling. During the research period, PTs travelled in groups to the schools where they were to perform their practicum. Lessons were video recorded, and PTs shared these recordings and their classroom experiences with their peers. As a result of the analysis, the study's findings were grouped into four main themes: (i) opinions regarding activities, (ii) opinions regarding preservice teachers, (iii) opinions regarding students, and (iv) opinions regarding mathematics teachers. Discussion of these findings revolved around both teacher training and mathematical modeling, which then led to several recommendations being made.
Keywords: Mathematical modeling; Preservice mathematics teachers; Mathematical modeling activities; Execution of activities; Mathematics education; EDUCATION; Education & Educational Research